2011
DOI: 10.2149/tmh.2011-s09
|View full text |Cite
|
Sign up to set email alerts
|

T-cell Responses to Dengue Virus in Humans

Abstract: Dengue virus (DENV) is a leading cause of morbidity and mortality in most tropical and subtropical areas of the world. Dengue virus infection induces specific CD4+CD8– and CD8+CD4– T cells in humans. In primary infection, T-cell responses to DENV are serotype cross-reactive, but the highest response is to the serotype that caused the infection. The epitopes recognized by DENV-specific T cells are located in most of the structural and non-structural proteins, but NS3 is the protein that is most dominantly recog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
21
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 27 publications
2
21
0
Order By: Relevance
“…Some studies have suggested a potential contribution of DENV-specific CD4 + T-cell responses to disease pathogenesis, while other studies have illustrated a potential protective role for this type of adaptive response [2][3][4]. DENV-specific CD4 + T cells were associated with direct effector cytotoxic function and, thus, have the potential to directly contribute to viral clearance by clearing DENV-infected macrophages that contribute to disease pathogenesis through the effects of antibody dependent enhancement [5][6][7].…”
mentioning
confidence: 99%
“…Some studies have suggested a potential contribution of DENV-specific CD4 + T-cell responses to disease pathogenesis, while other studies have illustrated a potential protective role for this type of adaptive response [2][3][4]. DENV-specific CD4 + T cells were associated with direct effector cytotoxic function and, thus, have the potential to directly contribute to viral clearance by clearing DENV-infected macrophages that contribute to disease pathogenesis through the effects of antibody dependent enhancement [5][6][7].…”
mentioning
confidence: 99%
“…Severe dengue infection also holds the virulence of DV as a devastating phenomenon for hemorrhage being a virologic factor. In addition, synergistic effects of mediators such as IL-2, IL-6, TNF, IFN-γ, PAF, complement C3a, C5a and histamine also provoke increased vascular permeability, plasma leakage, breakdown of the coagulation system and shock leading to hemorrhage [14,27].…”
Section: Discussionmentioning
confidence: 99%
“…The role of T lymphocytes in this process is controversial since on the one hand there is evidence that activation of T lymphocytes leads to pro-inflammatory cytokine synthesis [20,21,22,23,24,25,26,27] and on the other there is evidence that T-lymphocyte proliferation in dengue patients is impaired [28,29,30,31] and that patients with acute DENV infection are leukopenic [28,29]. Additionally, there are contradictory results as to whether T lymphocytes can be infected or not with DENV [41,42,43].…”
Section: Discussionmentioning
confidence: 99%
“…T lymphocytes play both effector and regulatory roles in the innate and adaptive immune responses, and several studies have shown that T lymphocytes are involved in the development of DHF/DSS [20]. In particular, cross-reactive memory T lymphocytes have been associated with changes in the vasculature, leading to vascular leakage [21,22,23], and activation of T lymphocytes during viremia, which is more evident in DHF, is reflected in the overproduction of cytokines [24].…”
Section: Introductionmentioning
confidence: 99%